Prevalence of impacted mandibular third molars among patients attending the dentomaxillofacial radiology clinic - Munjit Singh, Sanjit Singh; Sitam, Suhardjo; Sam, Belly (Padjadjaran Journal of Dentistry, 2013)
Introduction: The third molar is undoubtedly the most variable tooth in the human dentition, and also the most common tooth to become impacted due to it being the last tooth to erupt into the dental arch The aim of research is to obtain the prevalence of the mandibular third molar (M3) impaction among the patients attending the Radiology Clinic. Methods: The type of research conducted was a descriptive research. The sampling was purposive, drawn from a population of 1451 digital panoramic radiographs taken from January – December in the year 2010, of which 392 samples were included in the survey, with patient ages ranging between 18 – 59 years at time of exposure. The position of the M3’s was assessed using the Pell and Gregory and, Winter’s impaction classification. Results: The prevalence of impacted mandibular M3’s in this study is 76.8% overall. Of the impacted mandibular M3’s present, 76.1% were bilateral impactions and of these bilateral impactions 50.7% are similar in impaction classification. Of the mandibular M3’s examined, 40.1% are in a vertical angulation, 33.3% mesioangular, 23.5% horizontal and 3.1% distoangular. The three most common types of impaction according to the Pell and Gregory classification are IIB at 38.5%, IA at 36.8% and IIA at 18.8%. Conclusion: Prevalence of  mandibular third molar of the patients attending the Radiology Clinic is 76.8%.